Herbicide application in agriculture: nozzle selection and effective application - Chethan, C. R.; Singh, P. K.; Dubey, R. P.; Singhariya, S.; Choudhary, V. K. (Indian Farming, 2019)
Herbicides can be applied by a variety of means including boom sprayers, aerial spraying, misters, blanket wipers, rope wick applicators, weed seekers and back-pack sprayers. Boom sprayers are most common type of apparatus used for applying herbicides in broad-scale farming. The nozzle is the only component in the boom sprayer that directly determines the efficacy of the herbicide and effectiveness of spraying. All other components are necessary to position the nozzles and provide them with a continuous supply of herbicide at the correct pressure. The ideal nozzle-pressure combination should maximize spray efficiency by increasing deposition and transfer of a lethal dose to the target, while minimizing residues, off-target losses such as spray drift and user exposure. The droplet size and velocity distribution, volume distribution pattern, entrained air characteristics, spray sheet structure, and structure of individual droplets are such spray parameters, which influences efficiency of application of system. Spray droplet size is one of the most influential factors in spraying system, which affects crop coverage, biological efficacy of the applied herbicide and spray drift risk. Moreover, the size distribution of droplets in agricultural sprays is not homogeneous and depends on the position within the spray nozzle. Further, increasing the spray liquid pressure with most nozzle designs not only results in a finer spray but also increases the velocity of droplets leaving the region of spray formation. In general, increasing the initial downward droplet velocity decreases drift distances. Since spray becomes finer as pressure increases, the risk of drift tends to increase, however, some researchers found that a further increase in pressure does not result in a further increase of drift and may even, with some nozzle designs, result in a decrease in drift at high pressure due to the dominance of the droplet velocity effect.